Naturalistic outcomes of continuation right unilateral ultrabrief ECT in major depression: a retrospective chart review. (June 2020) - Atashnama, Azadeh; Aly, Husayn; Krishnan, Vijay; Howari, Rasha; Mayur, Prashanth
Objective: Continuation treatment of major depression following an acute course of electroconvulsive treatment (ECT) may be often required to prevent relapse. Data on continuation phase of right unilateral ultrabrief ECT are sparse and there are doubts if it is inherently capable of relapse prevention. Methods: All consecutive adult patients with major depression who received the first 'run' of continuation phase of right unilateral ultrabrief ECT over a 10-year period were routinely followed up. ECT frequency varied from weekly to up to once every 4 weeks for a maximum period of 6 months. The data were extracted from a retrospective chart review. Results: 20 out of 22 patients persisted with ultrabrief pulses (0.3 ms) with two needing 0.5 ms pulse widths. The median duration of continuation treatment was 51 days (range: 14–460). At the end of 1 month ( n = 17), treatment gap in days mean (SD): 10.18 (7.08), widening to mean (SD): 20.11 (16.85) at 4 months ( n = 9). Stimulus dose increased throughout the continuation phase: p = 0.026. In 16 out of 22 patients, more than 70% of the visits were charted as being 'in remission'. Conclusion: As most patients receiving ultrabrief ECT remained well, this study suggests that ultrabrief ECT can be used effectively in continuation therapy.